PENGEMBANGAN SISTEM DETEKSI KEBOCORAN GAS MENGGUNAKAN SENSOR MQ-2 DAN MICROCONTROLLER WEMOS D1 DENGAN SISTEM IOT - Khajar Afandi Putra, Khajar (Fakultas Teknik dan Ilmu Kelautan, Universitas Hang Tuah, 2024)
Flammable gas leaks such as Methane and Liquefied Petroleum Gas (LPG) pose serious risks of fire, explosion, and gas poisoning. This research develops a gas leak detection system based on the MQ-2 sensor, Wemos D1 microcontroller, and Internet of Things (IoT) technology. The system quickly and accurately detects gas leaks, provides automatic responses by shutting off gas flow via a solenoid valve, and activates a water nozzle valve for fire suppression. Real-time notifications are sent through the WhatsApp API. Testing showed response times of <5 seconds for gas leaks and <1 second for fires. The system is effective, real-time, and applicable in various environments